A Proposal for Viewing Government Open Data Information, Based on User Profiles - Assumpção, César Alencar [UNESP]; Brega, José Remo Ferreira [UNESP] (Springer Nature, 2021)
There is a global movement for the democratization of access to open government data, for the free use of society. This movement should enable greater participation by society in the development of a more efficient State, with the provision of public utility services, making wide use of technologies. To make this understanding clearer, a Systematic Literature Review (SLR) was carried out, which sought to reveal strategies for the use of open data, tools and techniques of Information Visualization. In Brazil, the municipalities are inspected by the State Audit Courts, and the São Paulo State Court of Auditors provides an open database of more than 600 municipalities. From this open database, complemented by other data sources and performance indicators, based on SLR results, the work presented in this article shows that with the correct application of Information Visualization techniques, it facilitates the understanding of public management. The public service is an important source of data, as it contains information that can have a direct impact on each citizen’s life and compromise essential services such as health, safety and education. What is intended again is to structure specialized presentations according to the user’s profile. The proposal is presented in the form of specific dashboards according to the user’s profile, which proved to be essential to add value to the information and improve the understanding of the interested parties.
Keywords: Information visualization techniques; OGD - Open Government Data; Open data; Visualization